Safety and immunogenicity of one versus two doses of Takeda's tetravalent dengue vaccine in children in Asia and Latin America: interim results from a phase 2, randomised, placebo-controlled study. Issue 6 (June 2017) - Sáez-Llorens, Xavier; Tricou, Vianney; Yu, Delia; Rivera, Luis; Tuboi, Suely; Garbes, Pedro; Borkowski, Astrid; Wallace, Derek
Summary: Background: Dengue is the most common mosquito-borne viral disease in human beings, and vector control has not halted its spread worldwide. A dengue vaccine for individuals aged 9 years and older has been licensed, but there remains urgent medical need for a vaccine that is safe and effective against all four dengue virus serotypes (DENV-1–4) in recipients of all ages. Here, we present the preplanned interim analyses at 6 months of a tetravalent dengue vaccine candidate (TDV), which is comprised of an attenuated DENV-2 virus strain (TDV-2) and three chimeric viruses containing the premembrane and envelope protein genes of DENV-1, DENV-3, and DENV-4 genetically engineered into the attenuated TDV-2 genome backbone (TDV-1, TDV-3, and TDV-4). Methods: An ongoing phase 2, randomised, double-blind, placebo-controlled trial of a TDV is being done at three sites in dengue-endemic countries (Dominican Republic, Panama, and the Philippines) to determine its safety and immunogenicity over 48 months in healthy participants aged 2–17 years who were randomly assigned (1:2:5:1) using an interactive web response system (stratified by age) to subcutaneous TDV injection (one 0·5 mL dose containing 2·5 × 10 4 plaque-forming units [PFU] of TDV-1; 6·3 × 10 3 PFU of TDV-2; 3·2 × 10 4 PFU of TDV-3; and 4·0 × 10 5 PFU of TDV-4) in different dose schedules (two-dose regimen at 0 and 3 months, one dose at 0 months, or one dose at 0 months and a booster at 12 months) or placebo. The primary endpoint of this 6 month interim analysis was geometric mean titres (GMTs) of neutralising antibodies against DENV-1–4 in the per-protocol immunogenicity subset at 1 month, 3 months, and 6 months after the first injection. Safety was assessed as a secondary outcome as percentage of participants with serious adverse events in all participants who were injected (safety set), and solicited and unsolicited adverse events (immunogenicity subset). This trial is registered withClinicalTrials.gov, numberNCT02302066 . Findings: 1800 participants were enrolled between Dec 5, 2014, and Feb 13, 2015. 1794 participants were given study injection as follows: 200 participants were given two-dose regimen at 0 and 3 months (group 1), 398 were given one dose at 0 months (group 2), 998 were given one dose at 0 months and will be given (trial ongoing) a booster at 12 months (group 3), and 198 were given placebo (group 4). These 1794 participants were included in the safety set; 562 participants were randomly assigned to the immunogenicity subset, of which 503 were included in the per-protocol set. TDV elicited neutralising antibodies against all DENV serotypes, which peaked at 1 month and remained elevated above baseline at 6 months. At 6 months, GMTs of neutralising antibodies against DENV-1 were 489 (95% CI 321–746) for group 1, 434 (306–615) for group 2, 532 (384–738) for group 3, and 62 (32–120) for group 4; GMTs of neutralising antibodies against DENV-2 were 1565 (1145–2140) for group 1, 1639 (1286–2088) for group 2, 1288 (1031–1610) for group 3, and 86 (44–169) for group 4; GMTs of neutralising antibodies against DENV-3 were 160 (104–248) for group 1, 151 (106–214) for group 2, 173 (124–240) for group 3, and 40 (23–71) for group 4; and GMTs of neutralising antibodies against DENV-4 were 117 (79–175) for group 1, 110 (80–149) for group 2, 93 (69–125) for group 3, and 24 (15–38) for group 4. No vaccine-related serious adverse events occurred; 15 (3%) of 562 participants in the immunogenicity subset reported vaccine-related unsolicited adverse events. The reactogenicity profile of TDV was acceptable, and similar to previous findings with TDV. Interpretation: TDV is safe and immunogenic in individuals aged 2–17 years, irrespective of previous dengue exposure. A second TDV dose induced enhanced immunogenicity against DENV-3 and DENV-4 in children who were seronegative before vaccination. These data supported the initiation of phase 3 evaluation of the efficacy and safety of TDV given in a two-dose schedule 3 months apart, with analyses that take into account baseline age and dengue serostatus. Funding: Takeda Vaccines.